Salicylic Acid Perturbs sRNA-Gibberellin Regulatory Network in Immune Response of Potato to Potato virus Y Infection - Križnik, Maja; Petek, Marko; Dobnik, David; Ramšak, Živa; Baebler, Špela; Pollmann, Stephan; Kreuze, Jan F.; Žel, Jana; Gruden, Kristina (Frontiers in Plant Science, 2017)
Potato virus Y is the most economically important potato viral pathogen. We aimed at unraveling the roles of small RNAs (sRNAs) in the complex immune signaling network controlling the establishment of tolerant response of potato cv. Désirée to the virus. We constructed a sRNA regulatory network connecting sRNAs and their targets to link sRNA level responses to physiological processes. We discovered an interesting novel sRNAs-gibberellin regulatory circuit being activated as early as 3 days post inoculation before viral multiplication can be detected. Two endogenous sRNAs, miR167 and phasiRNA931 were predicted to regulate gibberellin biosynthesis genes GA20-oxidase and GA3-oxidase. The increased expression of phasiRNA931 was also reflected in decreased levels of GA3-oxidase transcripts. Moreover, decreased concentration of gibberellin confirmed this regulation. The functional relation between lower activity of gibberellin signaling and reduced disease severity was previously confirmed in Arabidopsis-virus interaction using knockout mutants. We further showed that this regulation is salicylic acid-dependent as the response of sRNA network was attenuated in salicylic acid-depleted transgenic counterpart NahG-Désirée expressing severe disease symptoms. Besides downregulation of gibberellin signaling, regulation of immune receptor transcripts by miR6022 as well as upregulation of miR164, miR167, miR169, miR171, miR319, miR390 and miR393 in tolerant Désirée, revealed striking similarities to responses observed in mutualistic symbiotic interactions. The intertwining of different regulatory networks revealed, shows how developmental signaling, disease symptom development and stress signaling can be balanced.